(untitled) (Journal of actual problems of jurisprudence, 2016)
In this article problems of modernization of the legislation on labor unions are considered. From the date of declaration of independence of Kazakhstan labor unions are the participant of construction of new life, with their participation all acts in the sphere of the labor and social relations were adopted. Labor unions are a support of stability, Basic Element of the social and labor relations. The new tasks of active participation in Strategy realization are set for labor unions of Kazakhstan “Kazakhstan – 2050”. The President noted that the main objective is to create a republic in 2050 on the basis of the welfare society of a strong state, a developed economy and the possibilities of universal labor[1]..